Makna Kekudusan Hidup Menurut Imamat 19:2 Dan Implementasinya Bagi Kehidupan Rohani Persekutuan Pemuda Gereja Toraja Jemaat Sion Tiakka’ - Tapparan, Resvin; Tapingku, Joni; Lilo, Deflit Dujerslaim (Kharisma: Jurnal Ilmiah Teologi, 2022)
The problem of holiness of life among young people is often in the spotlight. The young generation is vulnerable to an attitude of life that does not reflect holiness. The holiness of life itself is emphasized in Leviticus 19:2 which is God's command to His people. To explore this research, the author will use qualitative research methods. Through literature study, the author conducted grammatical analysis while field research was conducted by means of observation and interviews. After doing research, the writer found that First, the meaning of the holiness of life stated in Leviticus 19:2 is related to God's commandments and the life principles of believers, both concerning moral matters and status before God. Second, the members of the Toraja Church Youth Fellowship (PPGT) of the Sion Tiakka' Congregation, Klasis Ulusalu have not understood and implemented the behavior of living in holiness according to God's will. Therefore, the meaning of the holiness of life based on Leviticus 19:2 can be applied to PPGT members of the Sion Tiakka Congregation in order to create a paradigm pattern and a holy life behavior. Permasalahan kekudusan hidup di kalangan anak muda sering menjadi sorotan. Generasi muda rentan dengan sikap hidup yang tidak mencerminkan kekudusan. Kekudusan hidup itu sendiri ditekankan dalam kitab Imamat 19:2 yang merupakan perintah Allah kepada umat-Nya. Untuk mendalami penelitian ini, Penulis akan menggunakan metode penelitian kualitatif.  Melalui studi kepustakaan, penulis melakukan analisis gramatikal sedangkan penelitian lapangan dilakukan dengan cara observasi dan wawancara. Setelah melakukan penelitian, penulis menemukan bahwa Pertama, makna kekudusan hidup yang dinyatakan di dalam Imamat 19:2 berkaitan dengan perintah Allah dan prinsip hidup orang percaya baik yang menyangkut urusan moral maupun status di hadapan Allah. Kedua, para anggota Persekutuan Pemuda Gereja Toraja (PPGT) Jemaat Sion Tiakka’, Klasis Ulusalu belum memahami dan menerapkan perilaku hidup dalam kekudusan sesuai kehendak Allah. Karena itu, makna kekudusan hidup berdasarkan Imamat 19:2 dapat diterapkan kepada anggota PPGT Jemaat Sion Tiakka’ agar terciptanya pola paradigma dan perilaku hidup yang kudus.